Adult Type Granulosa Cell Tumor: A Very Rare Case of Sex-Cord Tumor of the Testis with Review of the Literature - Dimosthenis Miliaras; Eleftherios Anagnostou; Ioannis Moysides (Case Reports in Pathology)
Granulosa cell tumor (GST) is a sex-cord/stromal neoplasm of the gonads, more commonly arising in the ovaries, while approximately 80 cases have been reported in the testes. Out of these, 30 cases were of the adult type, while the remainder 50 cases were of the juvenile type. The latter mostly concerned infants and followed a benign course. However, the adult type testicular GCTs may be potentially malignant as it also happens in female patients with such neoplasms. We present a case of an adult type GCT located at the left testis. The patient was subjected to total orchiectomy and received no further treatment. Histology showed typical GCT histomorphology with Call-Exner bodies in some places. The immunoprofile of the tumor was CD99 (+), calretinin (+), inhibin (+), alpha smooth muscle actin (+), vimentin (+), ER (−), PR (−), keratin AE1/AE3 (−), alpha fetoprotein (−), CD117 (−), and placental alkaline phosphatase (−). Two years after surgery, the patient is alive and well with no signs of recurrence.